On the Terminological Apparatus of Language Contacts in Modern Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In given article the basic terms framework of the contact linguistics, which are considered as one of new directions of modern linguistics, is in detail shined.